1999
DOI: 10.1891/0739-6686.17.1.133
|View full text |Cite
|
Sign up to set email alerts
|

The Chronobiology, Chronopharmacology, and Chronotherapeutics of Pain

Abstract: Data for this review of chronobiology, chronopharmacology, chronotherapeutics and pain were derived from electronic searches of the medical literature (Medline) utilizing both Silver Platter and OVID search engines. Further information was obtained from personal conversations with members of the International Society for Chronobiology involved in chronopharmacology and pain research and reviews of non-Medline-referenced materials and journals such as Chronobiologia and the Annual Review of Chronopharmacology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies indicate that the master clock that regulate the circadian activity rhythm is located in the hypothalamus i.e., in the suprachiasmatic nucleus (SCN) which regulates and controls the circadian activity and other circadian rhythms (Reppert et al , 2002; Herzog and Schwartz, 2002). It is known that medications as well as opioid can have different effects when administered at the morning compared to night administration (Auvil-Novak, 1999; Bruguerolle et al , 2007; Li et al , 2010). Opioids work through interaction with one of several receptors in the brain, specifically the μ (mu) type receptors, to produce analgesia (Smith et al , 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the master clock that regulate the circadian activity rhythm is located in the hypothalamus i.e., in the suprachiasmatic nucleus (SCN) which regulates and controls the circadian activity and other circadian rhythms (Reppert et al , 2002; Herzog and Schwartz, 2002). It is known that medications as well as opioid can have different effects when administered at the morning compared to night administration (Auvil-Novak, 1999; Bruguerolle et al , 2007; Li et al , 2010). Opioids work through interaction with one of several receptors in the brain, specifically the μ (mu) type receptors, to produce analgesia (Smith et al , 1995).…”
Section: Discussionmentioning
confidence: 99%
“…2 Current research shows an association in the timing of migraine headaches as preceding or coinciding with the onset of menstruation. 3 Ongoing research examines associations between the menstrual cycle and irritable bowel syndrome. 2 New research examines the associations between menstruation and pain.…”
Section: Research On the Menstrual Cyclementioning
confidence: 99%
“…Susan E. Auvil-Novak, R.N., Ph.D., while on the facul ty a t T he Fr ance s Payn e Bo lt o n School of Nursing, Case Western Reserve University, Cleveland, Ohio, was a lead investigator for several clinical studies on pain management. After revie wing 62 research studies on cycles and pain, 3 Dr. Auvil-Novak suggested that the traditional setting of 24-hour nursing care coverage provides a unique opportunity for clinical nursing research on biorhythms and pain. Asthma has a cyclic relation to the menstrual cycle.…”
Section: Chronobiology and Painmentioning
confidence: 99%
“…Circadian control of biologic events results in predictable daily patterns that characterize the function of most organ systems (e.g., pulmonary, cardiovascular, renal, hematologic, immunologic, cognitive, and motor function) and integrative physiologic functions (e.g., body temperature, blood flow) (3,4). Circadian rhythms also have been shown to influence the timing of disease processes.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional drug administration paradigms of flat infusions are not ideal to treat symptoms that fluctuate due to circadian rhythms or other causes. Instead, pulsed programmed drug delivery is required such that the desired amount of drug is delivered at different times to meet varying biologic needs (3). Within the last 30 years, the administration of drugs based on circadian rhythm patterns and other fluctuations has emerged as a possible way to improve treatment and reduce unwanted side effects for a number of diseases, including arthritis, ulcer disease, asthma, hypertension, and cancer (4).…”
Section: Introductionmentioning
confidence: 99%